2016
DOI: 10.1118/1.4947482
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of microwave ablation models to tissue biophysical properties: A first step toward probabilistic modeling and treatment planning

Abstract: Dielectric parameters, blood perfusion rate, and the temperature interval across which the tissue changes phase were found to have the most significant impact on MWA model outputs. The latent heat of tissue water vaporization and the volumetric heat capacity of the vaporized tissue were recognized as the least influential parameters. Uncertainties in model outputs identified in this study can be incorporated to provide probabilistic maps of expected ablation outcome for patient-specific treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 47 publications
0
55
0
Order By: Relevance
“…This premise is further supported by a recent computer modeling study, where MWA ablation zones varied only slightly when considering heterogeneity between tumor and normal tissue dielectric properties, compared to assuming homogeneous properties [9]. Additional studies have identified other heterogeneous tissue properties such as blood perfusion between tumor and normal tissue, to be a more relevant factor for accurate modeling of MWA than dielectric properties [9,38]. As such, the proposed approach affords inclusion of patient-specific blood perfusion in thermal models to address the growing interest in MWA treatment planning.…”
Section: Discussionmentioning
confidence: 90%
“…This premise is further supported by a recent computer modeling study, where MWA ablation zones varied only slightly when considering heterogeneity between tumor and normal tissue dielectric properties, compared to assuming homogeneous properties [9]. Additional studies have identified other heterogeneous tissue properties such as blood perfusion between tumor and normal tissue, to be a more relevant factor for accurate modeling of MWA than dielectric properties [9,38]. As such, the proposed approach affords inclusion of patient-specific blood perfusion in thermal models to address the growing interest in MWA treatment planning.…”
Section: Discussionmentioning
confidence: 90%
“…These models use numerical techniques to solve the partial differential equations which govern electromagnetic propagation, power deposition, and bioheat transfer to estimate the treatment zone following a defined microwave exposure . Recently, there has been renewed interest in the development of modeling techniques for predictive planning of ablation treatments . Currently, planning for MWA is done with vendor specification diagrams that provide estimates of expected ablation treatment region size as derived from experimental measurements, often conducted in nonperfused animal tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Although in this paper applications were focussed on hyperthermia, the software package is more widely applicable for electromagnetic and thermal simulations, for example in research on high field MRI, RF ablation, mobile phones or RF safety in general [100][101][102][103][104][105][106][107]. With the widespread use of MR investigations and the increasing field strength of MR scanners, safety aspects become very important and the risk of MR-induced hot-spots can be evaluated using simulations [106].…”
Section: Discussionmentioning
confidence: 99%